ANALISIS PENGARUH BAURAN PEMASARAN SYARIAH TERHADAP KEPUTUSAN MAHASISWA MEMILIH PRODI EKONOMI SYARIAH UNISKA MAB BANJARMASIN - Iman Setya Budi; Abdul Wahab; Zakiyah (Wahana Islamika: Jurnal Studi Keislaman, 2023)
Increasingly intense competition in the current era of globalization indirectly results in organizations always trying to maintain their existence in society. Rapid and dramatic environmental developments and changes, including changes in consumer tastes, technological advances, and socio-economic changes, have affected the higher education sector, resulting in intense business competition in the higher education industry. Efforts to increase competitive advantage can be made by implementing a Sharia marketing mix strategy. This study aims to examine and determine the effect of the Sharia marketing mix on students' decisions to choose the Islamic Economics study program either partially or simultaneously. This research includes field research by exploring data from research locations, namely students of the Islamic Economics Study Program at UNISKA MAB Banjarmasin. Data collection was carried out using a questionnaire with a measurement scale, a Likert scale, and documentation. Determination of the sample using probability sampling technique, namely using simple random sampling with a total sample of 83 respondents and research data analysis using multiple linear regression analysis. The results of the study show that: 1) Partially, the variables Product, Promotion, Place, People, and Physical Evidence have a significant effect on the Student's Decision to Choose an Islamic Economics Study Program. While the Price and Process variables have no significant effect in this study. 2) Simultaneously, there is a significant influence of the Sharia marketing mix on the Student's Decision to Choose the Islamic Economics Study Program with a score of 81.020 with sig. F = 0.000 (p < 0.05).